Peran Pemerintah dan Pembangunan Sosial sebagai Pemenuhan Hak Asasi Rakyat - Suharto - (Unisia, 2002)
Since at the end of decade of the twentieth century, the trends of the strength of the market economy regime, the intervention of government in economic face the pressure. In the context of development, the pressure in minimizing government intervention be cause of the proof regarding the failure in conducting its role. The development of economy increases the growth of economy without able to overcome the problem of the chasm and the poverty. The problems as mentioned above raise because development of economy does not equalize social development. To liberate society from poverty constitutes the actualization of filling human right. Accordingly, the social role of government in abolishing poverty denotes the human obligation rights that should be carried out by government.